2014
DOI: 10.1002/anie.201308431
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Computational Study of a Nonheme Iron Nitrosyl Center in a Biosynthetic Model of Nitric Oxide Reductase

Abstract: A major barrier to understanding the mechanism of nitric oxide reductases (NORs) is the lack of selective probe of NO binding to the non-heme FeB center. By replacing the heme in a biosynthetic model of NORs (L29H/F43H/V68E Mb), that structurally and functionally mimics NORs, with isostructural ZnPP, we report herein a study where the electronic structure and functional properties of the FeB-nitrosyl complex has been probed selectively. This approach allowed us to observe the first S=3/2 non-heme {FeNO}7 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 54 publications
3
54
0
Order By: Relevance
“…have concluded that the investigated S =3/2 {FeNO} 7 species can be described as a HS ( S =2) ferrous Fe II antiferromagnetically coupled with NO ( S =1/2 ) . The same conclusion was drawn from a recent spectroscopic and computational study of a non‐heme iron‐ nitrosyl center in a biosynthetic model of nitric oxide reductase …”
Section: Introductionsupporting
confidence: 74%
“…have concluded that the investigated S =3/2 {FeNO} 7 species can be described as a HS ( S =2) ferrous Fe II antiferromagnetically coupled with NO ( S =1/2 ) . The same conclusion was drawn from a recent spectroscopic and computational study of a non‐heme iron‐ nitrosyl center in a biosynthetic model of nitric oxide reductase …”
Section: Introductionsupporting
confidence: 74%
“…Since the CV signals from redox-active heme iron could interfere with those of the nonheme metal, we replaced heme with redox-inactive Zn protoporphyrin to obtain Fe B Mb(Zn II ) using a previously reported protocol. 31 The titration of Fe II and Cu I metals into the Fe B center of Fe B Mb(Zn II ) resulted in similar changes in the Soret and visible bands of the UV-Vis spectra, suggesting similar coordination environments of nonheme Fe II and Cu I in Fe B Mb(Zn II ) (Supplementary Fig. S6).…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, no synthetic model of NOR exhibits more than a single turnover of NO reduction. In this work, we utilize a myoglobin (Mb)-based structural and functional model of NOR (23)(24)(25)(26)(27)(28) to investigate the impact of tuning heme E°′ on NOR functionality. The structural simplicity of Mb makes it amenable to a variety of modulations for redox tuning: the H-bonding interaction to the proximal ligand of the heme iron can be readily tuned in Mb through site-directed mutagenesis of nearby amino acid residues (29).…”
Section: Significancementioning
confidence: 99%